Pengaruh Model Pembelajaran Flipped Problem Based Learning Terhadap Kemampuan Berpikir Kritis Siswa - Prasetyo, Yogi; Yurniwati, Yurniwati; Nurjannah, Nurjannah (Jayapangus Press, 2025)
Critical thinking skills are one of the essential abilities that every student needs to possess in order to face the challenges of the ever-changing times. However, the opposite is often found, as various difficulties and obstacles lead to low levels of students' critical thinking skills. This study aims to analyze the effect of the flipped Problem-Based Learning (PBL) model on students' critical thinking skills in fifth-grade mathematics at elementary schools. The method employed was experimental (quasi-experiment) with a posttest-only control group design. Data were collected using a test instrument in the form of essay questions. Data analysis was conducted through normality tests, homogeneity tests, and t-tests to examine the differences in the average critical thinking skills of each group, assisted by SPSS version 27. The t-test results showed a significance value of 0.012, which is lower than 0.05, indicating that the hypothesis is accepted. The findings revealed a significant difference in students' critical thinking skills between the group using the flipped PBL model and the group using the expository model. This research demonstrates that students who learned using the flipped PBL model exhibited better critical thinking skills compared to those who learned using the expository model.